Understanding Medical Mistrust in Black Women at Risk of BRCA 1/2 Mutations - Sutton, Arnethea L. (J Health Dispar Res Pract, 2019)
The benefits of genetic counseling and testing for hereditary breast and/or ovarian cancer (HBOC) are well documented; however, Black women are less likely to use these services compared to White women. Mistrust of the medical system has been associated with Black women’s use of genetic counseling and testing (GCT). However, relatively little is known about the correlates of medical mistrust in Black women at increased risk of HBOC. In this study, we examined the prevalence and predictors of medical mistrust in 94 Black women at-risk of HBOC. Most women were married (48.7%) and had at least some collegiate education (57.1%). While no predisposing characteristics were significantly related to medical mistrust, bivariate analysis indicated significant relationships between mistrust and fatalism (p=0.04), perceptions of discrimination in the healthcare setting (p=0.01), and self-efficacy in obtaining GCT (p=0.01). Multivariable analysis revealed that women who reported more discriminatory experiences and women with less confidence in obtaining GCT expressed greater medical mistrust. Multilevel approaches are needed to address psychosocial factors associated with feelings of mistrust. Future efforts must not solely focus on educating women on the importance of and need for GCT; addressing structural barriers, such as patient-provider interactions, that contribute to mistrust must become a priority.